Otimalisasi Potensi Ekonomi Lokal: Strategi Penguatan Dan Implikasi Positif Peran Umkm Kelurahan Made Kota Surabaya - Yola Erlanda; Ghulam Maulana Ilman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Made Village in Surabaya City has diverse economic potential, especially in the Micro, Small and Medium Enterprises (MSME) sector. This potential includes local products, handicrafts, traditional food, and tourism. MSMEs in Made Village include the processing of sengon nuts and soy milk. However, there are opportunities to develop these MSMEs through appropriate strengthening strategies. Strengthening MSMEs in Made Village through approaches such as skills training, increasing market access through digital platforms, developing collaboration networks, and implementing information technology can be strategic steps to increase the competitiveness and growth of MSMEs. This research uses a qualitative descriptive method. The author uses secondary research data sources to support research obtained from print and electronic media. Secondary data is a previously existing data source, obtained by researchers indirectly through intermediary media. With diverse economic potential, especially in the Micro, Small and Medium Enterprises (MSME) sector. From the author's short interview with MSME partners, sengon bean and soy milk entrepreneurs. Strategy efforts to strengthen MSMEs in Made Village, Surabaya City start from ensuring the quality of the products or services offered remains superior, to maintaining good relationships with customers. This also includes monitoring the market and being flexible to changing trends and consumer needs. What is no less important is paying attention to operational efficiency and managing finances wisely to maintain the financial health of entrepreneurs. Strategic efforts are needed to strengthen such as developing local partnerships, community empowerment, promotion and marketing, product diversification and access to financing. Apart from that, the government needs to make efforts to support MSMEs through Article 97 of the Job Creation Law. The government allocates funds to the community to help MSMEs to operate and reach the market. thus providing positive implications for entrepreneurs (MSMEs) and local residents. Advice from researchers for MSME business actors to innovate more creatively and keep up with current developments by utilizing the latest technology, and also involving local residents to participate in improving the local economy.